Security of Networks and Services in an All-Connected World 11th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2017, Zurich, Switzerland, July 10-13, 2017, Proceedings - Tuncer, Daphne; Koch, Robert; Badonnel, Rémi; Stiller, Burkhard (Computer Communication Networks and Telecommunications, 2017)
This book is open access under a CC BY 4.0 license. This book constitutes the refereed proceedings of the 11th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2017, held in Zurich, Switzerland, in July 2017. The 8 full papers presented together with 11 short papers were carefully reviewed and selected from 24 submissions. The papers are organized in the following topical sections: security management; management of cloud environments and services, evaluation and experimental study of rich network services; security, intrusion detection, and configuration; autonomic and self-management solutions; and methods for the protection of infrastructure.